Desafios na efetivação da democracia participativa no Brasil: o caso do Decreto no 8.243/14 - Nascimento, Rayanne Odila Ribeiro do (2021)
The participation and democratic theory is, in Brazil, a constitutional project to which the historic popular mobilization, especially in the Assembleia Nacional Constituinte, contributed decisively. However, despite such seed crystallized in the Carta de 88, the factual concreteness demonstrates the existence of countless actors hindering not only the multiplication of channels of dialogue with society, but the construction of a broad democratic process. In this sense, this research seeks to understand, from the analysis of the trajectory of Decree no 8.243/14 (responsible for instituting the National Policy for Social Participation - PNPS and the National System for Social Participation), which are the major challenges currently encountered in the implementation of participatory democracy in Brazil. Therefore, the research is divided into three stages. In the first, study the concept of democracy and its representative and participatory modalities, examining the way in which the participatory paradigm was inserted in Brazil. Then, the study of the constitutional provisions related to the expansion of community participation and also the integrality of Decree no 8.243/14, both in its formulation and in its final text. The third and last moment of the research, finally, turns to the study of the media, political and ideological bombardment faced by the aforementioned normative that sought to delegitimize it, understanding the performance of such actors not as directed to a specific rule of law, but, yes, as a symptom of a larger process: the weakening (or extermination) of popular participation in Brazil. In this sense, the methodological aspects use of the qualitative approach and the dialectical paradigm as an epistemological assumption, as well as the case study as a method of designing and planning the operations necessary to carry out the research.